Representations of Coloured identities on the Witwatersrand Reef: No Room for Squares and Umm...Somebody Say Something - Norman, Mxolisi Vincent (My University, 2009)
This thesis investigates the representation of Coloured identities on the Johannesburg Reef. The study proceeds from the premise that colonial /apartheid apprehensions of the Coloured subject were significantly limited to the physicality of the body. Central to such apprehensions were dominant ideologies which served to propagate socio-political control. Representations of, and resultant discourses on Coloured identities often reproduce this colonial/apartheid racial imaginary. Contemporary meanings of national identity in South Africa exhibit an aversion to historical notions of race. The ‘rainbow nation’ imaginary, is an ‘official’ performance of this desire. The Coloured identity seems implicated in ‘official’ processes of elimination This research report proposes an alternative reading of Colouredness, which reading is largely informed by postmodern concepts of identity. The postmodern paradigm conceives of identity as a complex configuration beyond racial indices. The central argument in this thesis is that Colouredness is a postmodern state that informs all contemporary identities.